The Parenting Styles and Impact on Temper Tantrums in Early Childhood - Farazia Rezki Putri; Eva Latipah (JOYCED: Journal of Early Childhood Education, 2022)
Temper tantrums are angry reactions from early childhood that often occur when children show negative attitudes. This study aims to determine how the effect of parenting on temper tantrums in early childhood at RA Al-Azhar Langsa. This type of research is field research with a qualitative approach. Sources of data used are people who are the target of research, namely children, teachers, and parents. The data collection technique used is observation followed by interviews. To compose a research analysis, three lines of activities co-occur data reduction, presentation of three data, and concluding/verification. The author can suggest that parents can use appropriate parenting patterns to overcome children's temper tantrum behavior because there are positive things that can be seen from children's temper tantrum behavior. Namely, with temper tantrums, the child wants to show independence, desire, expression of expression, and frustration.